Disinfection of Needleless Connector Hubs: Clinical Evidence Systematic Review - Nancy L. Moureau; Julie Flynn (Hindawi Limited, 2015)
Background. Needleless connectors (NC) are used on virtually all intravascular devices, providing an easy access point for infusion connection. Colonization of NC is considered the cause of 50% of postinsertion catheter-related infections. Breaks in aseptic technique, from failure to disinfect, result in contamination and subsequent biofilm formation within NC and catheters increasing the potential for infection of central and peripheral catheters. Methods. This systematic review evaluated 140 studies and 34 abstracts on NC disinfection practices, the impact of hub contamination on infection, and measures of education and compliance. Results. The greatest risk for contamination of the catheter after insertion is the NC with 33-45% contaminated, and compliance with disinfection as low as 10%. The optimal technique or disinfection time has not been identified, although scrubbing with 70% alcohol for 5-60 seconds is recommended. Studies have reported statistically significant results in infection reduction when passive alcohol disinfection caps are used (48-86% reduction). Clinical Implications. It is critical for healthcare facilities and clinicians to take responsibility for compliance with basic principles of asepsis compliance, to involve frontline staff in strategies, to facilitate education that promotes understanding of the consequences of failure, and to comply with the standard of care for hub disinfection.